Use it and bruise it: copulation rates are associated with muscle inflammation across anole lizard species. (17th March 2021) - Martin, K. S.; Kahrl, A. F.; Ivanov, B.; Johnson, M. A.
Abstract: The use of skeletal muscles causes cellular damage, a process that leads to inflammation. Although this process is well studied in mammals, it is largely unexplored in other taxa, and the behavioral use of a muscle has not been linked to muscle inflammation in a comparative framework. In this study, we examined the relationship between muscle use and inflammation across 22 anole lizard species. We tested the hypothesis that inflammation in the retractor penis magnus (RPM), a muscle used only during mating, is positively associated with copulation rate and/or with hemipenis size. We measured copulation rates for each species in the field and measured RPM inflammation for both wild‐caught males and, for one species, captive virgin male anoles. We found a positive relationship between RPM inflammation and copulation rate, yet there was no correlation between RPM inflammation and hemipenis size or body size. This finding supports the generality of the relationship between muscle use and inflammation within and across species, suggesting that inflammation could act as a snapshot of recent muscle activity across vertebrate taxa. Abstract : In mammals, using a muscle results in inflammation of the muscle tissue, but it is not clear whether this occurs in other animals. In this study, we examined 22 species of anole lizards, measuring inflammation in a muscle used in copulation and frequency of copulation in the field. We found that species that copulate more frequently exhibit greater inflammation in the copulatory muscle, suggesting that inflammation is a general response to muscle use that may provide a snapshot of recent behavioral activity.